2020
DOI: 10.1002/bies.201900220
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Views of Tuberculosis: Indoleamine 2,3‐Dioxygenase Catalyzed Nicotinamide Synthesis Reflects Shifts in Macrophage Metabolism

Abstract: Indoleamine 2,3-dioxygenase (IDO) is the rate-limiting enzyme in conversion of tryptophan to kynurenines, feeding de novo nicotinamide synthesis. IDO orchestrates materno-foetal tolerance, increasing human reproductive fitness. IDO mediates immune suppression through depletion of tryptophan required by T lymphocytes and other mechanisms. IDO is expressed by alternatively activated macrophages, suspected to play a key role in tuberculosis (TB) pathogenesis. Unlike its human host, Mycobacterium tuberculosis can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 118 publications
(151 reference statements)
0
16
0
1
Order By: Relevance
“…It has been reported that AhR-deficient macrophages showed a higher level of proinflammatory cytokines upon LPS stimulation and that AhR-deficient mice were more susceptible to LPS-induced lethal shock than wild-type mice [96]. Recently, Suchard et coworkers [97] summarized existing literature and showed that elevated IDO1 activity is regarded as a feature of M2 macrophage activation.…”
Section: Ido1 and Monocytes/macrophagesmentioning
confidence: 99%
“…It has been reported that AhR-deficient macrophages showed a higher level of proinflammatory cytokines upon LPS stimulation and that AhR-deficient mice were more susceptible to LPS-induced lethal shock than wild-type mice [96]. Recently, Suchard et coworkers [97] summarized existing literature and showed that elevated IDO1 activity is regarded as a feature of M2 macrophage activation.…”
Section: Ido1 and Monocytes/macrophagesmentioning
confidence: 99%
“…As prokaryotes, bacteria have their own unique pathways of NAD synthesis. Commensal and pathogenic flora form a complex cycle of NAD synthesis and consumption, which may regulate the pathogen-host balance [63] [19]. As an example, tuberculosis necrotizing toxin, secreted by Mycobacterium tuberculosis, with homologues in many bacterial and fungal pathogens, hydrolyses NAD + and results in cellular death by necroptosis [64].…”
Section: Interaction Of Infectious Organisms With De Novo Nicotinamidmentioning
confidence: 99%
“…As an example, tuberculosis necrotizing toxin, secreted by Mycobacterium tuberculosis, with homologues in many bacterial and fungal pathogens, hydrolyses NAD + and results in cellular death by necroptosis [64]. Mycobacterium tuberculosis can also synthesize niacin [65], leading to postulates that latent Mycobacterium tuberculosis has beneficial effects for the human host by increasing nicotinamide availability [66] [63].…”
Section: Interaction Of Infectious Organisms With De Novo Nicotinamidmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting ratio of kynurenine to tryptophan (K/T) has therefore been proposed as a potential biomarker for the diagnosis of TB that was also associated with treatment outcomes. The decline in tryptophan is associated with the induction of immunoregulatory enzyme indoleamine 2,3-dioxygenase (IDO-1), which breaks down tryptophan to kynurenine metabolites and suppresses the immune response, particularly through shifts in macrophage metabolism and induction of T-cell anergy and apoptosis ( 8 , 9 ). Metabolic changes in this pathway have also been identified among those with latent TB infection, as well as in multidrug-resistant TB, cavitary disease, and extrapulmonary TB, with low tryptophan in the cerebrospinal fluid of people with tuberculous meningitis ( 7 , 10 ).…”
Section: Introductionmentioning
confidence: 99%